ANALYZING WOMEN’S LANGUAGE FEATURES USED BY LISA ALLARDICE IN HER NEWS ARTICLES - Maria Ludwina Maharani Paila (ELTR Journal, 2022)
The study deals with women’s language features used by Lisa Allardice in her news articles that were uploaded in UK daily newspaper, The Guardian. The aim of this study is to analyse the women’s language features using Lakoff’s theory and the dominant feature that Lisa Allardice used in her news articles. The data were collected from three selected news articles using document analysis and described using qualitative method. The first article entitled Can Objects Teach Us about Reality?’: Ruth Ozeki on Her Women’s Prize-Winning Novel, the second article entitled The King and Queen of Popular Fiction: Marian Keyes and Richard Osman on Their Successes and Struggles, and the last article entitled Candice Carty-Williams: “It’s Time to Write a Book Just about Black People”. The findings showed that there are 6 women’s language features with 74 data. Kind of women’s language features that were found are lexical hedges or fillers, empty adjectives, precise colour terms, intensifiers, hypercorrect grammar, and emphatic stress. The dominant feature used by Lisa Allardice is hypercorrect grammar.